Surgeon and hospital cost variability for septoplasty and inferior turbinate reduction. Issue 10 (20th July 2016) - Thomas, Andrew; Alt, Jeremiah; Gale, Craig; Vijayakumar, Sathya; Padia, Reema; Peters, Matthew; Champagne, Trevor; Meier, Jeremy D.
Abstract : Background: Septoplasty and turbinate reduction (STR) is a common procedure for which cost reduction efforts may improve value. The purpose of this study was to identify sources of variation in medical facility and surgeon costs associated with STR, and whether these costs correlated with short‐term complications. Methods: An observational cohort study was performed in a multifacility network using a standardized cost‐accounting system to determine costs associated with adult STR from January 1, 2008 to July 31, 2015. A total of 4007 cases, performed at 21 facilities, by 72 different surgeons were included in the study. Total costs, variable costs, operating room (OR) time, and 30‐day complications (eg, epistaxis) were compared among surgeons, facilities, and specialties. Results: Total procedure cost: (mean ± standard deviation [SD]) 2503 ± 790 (range, 852 to 10, 559). Mean total variable cost: 1147 ± 423 (range, 400 to 5, 081). Intersurgeon and interfacility variability was significant for total cost ( p < 0.0001) and OR time ( p < 0.0001). Intersurgeon OR supply cost variability was also significant ( p < 0.0001). Otolaryngologists had less total cost ( p < 0.0001), OR time/cost ( p < 0.0001), and complications ( p = 0.0164), but greater supply cost ( p < 0.0001), than other specialties. Conclusion: There is wide variation in cost associated with STR. Significant variance in OR time and supply cost between surgeons suggests these are potential areas for cost reduction. Although no increased 30‐day complications were seen with faster and less costly surgeries, further research is needed to evaluate how time and cost relate to quality of care.